Integration of Exchange Rate and Stock Market : Evidence from the Indian Stock Market - Yadav, Sachita (Indian Journal of Finance, 2016)
The stock market represents the financial health of an economy, while the exchange rate represents the country’s currency value against the value of international currency. After economic reforms in India post 1991, the economic and overall growth got a boom because of globalization and privatization. These reforms enhanced the imports and exports and brought volatility in the exchange rate. The current research work investigated the rapport among Nifty index returns in India and the Indian exchange rate in consideration with the U.S. dollar. The exchange rate volatility generates volatility in the stock market, which creates confusion in the minds of domestic investors as well as for foreign institutional investors. The main purpose of conducting this research was to find out the impact of change in the exchange rate in India on the trading volume and returns of Nifty index. To examine the relationship between stock market returns and exchange rate, econometric tools like ADF test, correlation, Johansen’s co-integration test, and Granger causality test were applied with the help of EVIEWS program. The study was conducted during the period from April 2005 till March 2014. The empirical analysis showed that negative correlation existed among the stock market returns and exchange rate; however, the degree of correlation was not very significant. Co-integration test results showed that there was an absence of co-integration among the variables. The Granger causality test indicated that Nifty stock returns Granger caused the rupee-dollar exchange rates in India. This paper provides suggestions to the investors regarding the strategies that they can opt for trading in volatile stock markets to minimize risk or fear of bearing losses.